The cautious faculty: Malaysian university researchers’ awareness, experiences, and attitudes towards Open Peer Review - Hodonu-Wusu, James Oluwaseyi; A., Noorhidawati; A., Abrizah (Malaysian Journal of Library and Information Science, 2021)
The rationale of open peer review (OPR) is transparency as a general concept, where authors and reviewers’ identities are revealed and/or the reviews are published with the article. It is unclear whether there is an uptake for OPR from non-western researchers, given that there has been a geographical disparity in traditional peer review where non-western nations are under presented. As such, this study investigates the awareness, experiences, and attitudes of researchers in regard to OPR, which is part of a larger study that concentrated on the scholarly communication readiness of Malaysian researchers in open science. The data were gathered by means of a survey which obtained 135 responses from researchers based in five research universities in Malaysia. The main findings suggested that (a) attitudes towards OPR are reasonably positive with moderate levels of understanding and practices; (b) low awareness on open identities, open interactions and open reports traits of OPR; (c) a stronger levels of OPR experience amongst the sciences and younger researchers; and (d) the majority still have strong concerns about the transparency traits of OPR. The study concludes that OPR is not yet taking root among researchers from this emerging nation.